The impact of public transport policies on the efficiency of operating companies: a comparison between European countries - Duarte Monedero, Beatriz; Álvarez Jiménez, Isabel María; Sánchez Toledano, Joaquín; Simón de Blas, Clara (Transformations In Business & Economics, 2026)
Achieving sustainable mobility is widely regarded as one of the major challenges in contemporary public management. Governments must lead policies that facilitate progress towards sustainable, accessible, and efficient mobility. The European Union (EU) has identified the attainment of sustainable mobility as a key objective, with the first White Paper on transport being published in 1992. The main EU member states have implemented this roadmap to varying extents via different regulatory frameworks. In urban and metropolitan areas of large cities, the need to develop comprehensive mobility policies is particularly evident, as these areas face substantial challenges pertaining to environmental impact, public health, accessibility, and economic management. The governance of interurban transport (both passenger and freight) must also address these challenges while fostering social and territorial inclusion. In both cases, the transition towards a new paradigm of sustainable mobility necessitates a reduction in private vehicle usage and the promotion of a public transport system. This sector is crucial to the economy, accounting for nearly 10% of the EU’s gross value added and generating approximately 11 million jobs. Transport policies directly impact operators in the sector across multiple dimensions, including management, efficiency, profitability, and investment planning. Therefore, this study aims to analyse the impact of transport policies on the efficiency of urban and suburban transport companies in EU countries. The methodology employed consists of (1) a description of the main variables of these companies, (2) a Data Envelopment Analysis and Malmquist Index to provide statistical inference estimators for productivity, Efficiency Change (EFCH) into Pure Technical Efficiency Change (PTECH), and Scale Efficiency Change, and (3) a regression analysis linking efficiency to transport policies in the EU country members. The present study contributes to the academic literature and proposes theoretical and practical implications for the various stakeholders involved in the management of the transport sector.